FEATURES OF THE HYGIENIC-CULTURAL APPROACH TO PRODUCT PRODUCTION - Nilufar Niyozova (Western European Studies, 2024)
This article reveals the essence of economic production, hygienic requirements, quality and main criteria of products in the field of human health protection
Keywords: Economics; hygienic culture; human health